The Disclosure of Akhlak Core Values: Social Responsibility Practice PT. Bank Syariah Indonesia Supporting SDG 16 - Siti Jubaedah; Djoko Suhardjanto; E. Muhtar E. Muhtar; Setianingtyas Honggowati (Journal of Current Studies in SDGs, 2027)
Objective: To examine the disclosure of akhlak core values in corporate social responsibility (CSR) practices at PT Bank Syariah Indonesia. The study highlights how Islamic ethical values contribute to responsible corporate practices and support Sustainable Development Goals (SDGs), particularly SDG 16 related to strengthening accountable and ethical institutions. Method: A quantitative research method using an interpretive paradigm with a phenomenological approach. Data were collected through structured and semi-structured interviews with managers of LAZNAS Bangun Sejahtera Mitra Umat and CSR program beneficiaries. Secondary data were obtained from institutional reports of LAZNAS Bangun Sejahtera Mitra Umat. Data analysis was conducted to understand the meaning and implementation of akhlak core values within CSR activities.  Results:  The findings reveal that akhlak core values are aligned with universal Islamic values based on the Al-Qur’an and Hadith. The disclosure of these values is reflected through three CSR pillars: educating the people, partnering with the people, and sympathizing with the people. Furthermore, six dimensions of akhlak values were identified: trustworthy, competent, harmonious, loyal, adaptive, and collaborative. Novelty: The study contributes to CSR and Islamic accounting literature by exploring ethical value disclosure as a foundation for sustainable corporate responsibility practices. The findings provide insights into how Islamic ethical principles can strengthen corporate accountability and support sustainable institutional development.